O artesanato como tema gerador para o ensino de ciências : uma perspectiva freireana - Silva, Jaime Rodrigues da (2017)
The problematic that involves science/chemistry teaching/learning in some brazilian elementary school units that insist on remaining with the traditional/rationalistic/ technicist way of teaching, repetition and memorization of content, turns teachers and students In mere figures imprisoned in a textbook. This action does not meet the local social, environmental, ethical, political and economic demands that are necessary to seek to improve the quality of life of the community. In this context, the creation of didactic sequences using Contextualization, CTS curriculum and Multiculturalism Interculturalism, is fundamental to motivate learners to know their culture, as well as to involve social, political and technological aspects in order to build Time a citizen attitude. The general objective of this research is to study the possibilities and limitations of the use of handicrafts, as a generative theme to facilitate the learning in sciences, in an urbanrural school in the municipality of Penedo, in the state of Alagoas, from a Freirean perspective. Because it is a region, that the inhabitants over time appropriated knowledge of different peoples, the question of the affirmation of identities and power relations between the different cultures, with the questioning of prejudices and discriminations, made the study relevant to the school and to the community at large. To promote the reflection of this new perspective of work, we use as strategy a Case Study, according to Sá, Francisco and Queiroz (2007). The teacher's role in this new proposal will be to articulate knowledge / knowledge / information through a generative theme, made by a Freirean Thematic Approach, which is so necessary in function of the social context designed in the region, but which runs up against the imposed resistances Government policies. In the theoretical basis of the research, we highlight: Vygotsky with the implications of the Zone of Proximal Development (ZPD); Delizoicov, Angotti and Pernambuco, with the adaptation of the Generative Theme for the teaching of sciences; Laraia and Geertz, through the conception about culture; Figueiredo, Candau and Canen and the perspectives of working with multicultural / intercultural issues in school. From the analysis of data it was possible to conclude that it is necessary to work with interpretation of texts so that the apprentices can take the scientific knowledge and apply them in their daily life, but with the intervention: "Save the Taboa in Penedo / Alagoas" Made clear the importance of valuing traditional knowledge and knowledge and relating it to the scientist in an attempt to create a school closer to the context in which boys and girls live.